Rethinking cultural capital and community-based arts. (June 2013) - Khan, Rimi
This article examines the contemporary field of Australian community-based arts in light of Bourdieu's work on cultural capital. It considers how questions of ethnicity have complicated the field of community-based arts and informed the experience of artists and participants. These questions have implications for what it is that these organisations seek to do; specifically, the sorts of 'capital' they impart to participants in their programs, and what the significance of such capital is. Articulating a critical notion of cultural capital – and one that can accommodate the knowledges and competences that are relevant to the contemporary Australian context – can contribute to a more nuanced understanding of the role such arts organisations have in redefining or contesting the hierarchies of value that inform the art field.